The Biphasic Effect of Lipopolysaccharide on Membrane Potential - Maria E. Hadjisavva; Robin L. Cooper (Membranes)
Lipopolysaccharide (LPS) from certain strains of Gram-negative bacteria can induce a rapid (<1 s) hyperpolarization of membrane potential, followed by a gradual depolarization exceeding the initial resting membrane potential. Through overexpression of a Drosophila ORK1 two-pore-domain K+ channel (K2P) in larval muscles and altering the external concentrations of K+ and Na+ ions, it is clear that the hyperpolarization is due to activating K2P channels and the depolarization is due to promoting an inward Na+ leak. When the external Na+ concentration is negligible, the LPS-delayed depolarization is dampened. The hyperpolarization induced by LPS can exceed −100 mV when external K+ and Na+ concentrations are lowered. These results indicate direct action by LPS on ion channels independently of immune responses. Such direct actions may need to be considered when developing clinical treatments for certain forms of bacterial septicemia.